Rethinking Athens Before the Persian Wars: Proceedings of the International Workshop at the Ludwig-Maximilians-Universität München (Munich, 23rd–24th February 2017) - Graml, Constanze; Doronzio, Annarita; Capozzoli, Vincenzo (utzverlag GmbH, 2020)
In recent years, scholarly interest in Ancient Athens has been enlivened by spectacular archaeological discoveries. The new finds from the pre-Classical city called for a synoptic reassessment of the material remains, their interpretation and the previous methodological approaches, since the dense records of later historical phases had shaped the perception of Athens before the Persian Wars. Under theses premises, the International Workshop held at the Ludwig-Maximilians-Universität München in February 2017 invited its participants to rethink early Athens. The papers assembled in this volume aim to question traditional perspectives and offer a multidisciplinary framework for the discussion of archaeological, literary and epigraphical testimonia. Reihe Münchner Studien zur Alten Welt - Band 17